Níveis plásmáticos de vitamina D em indivíduos atendidos em unidades básicas de saúde em um município de pequeno porte - Farias, Marluza Ferreira (2025)
Vitamin D is a liposoluble prohormone essential for bone metabolism and plays important immunomodulatory roles in the human body. However, methodological heterogeneity among studies has raised questions about the favorable outcomes related to its routine supplementation. Nevertheless, vitamin D deficiency or insufficiency—especially in vulnerable populations—represents a significant public health challenge, even in regions with abundant sunlight exposure and well-structured primary care systems. This dissertation addresses the topic across three chapters. The first presents a literature review contextualizing the evidence regarding the mechanism of action, plasma levels, benefits, and adverse effects associated with vitamin D. In summary, this chapter reinforces the importance of vitamin D for human health, highlighting robust evidence for the benefits of its supplementation in specific and non-routine conditions. It also emphasizes the high prevalence of deficiency or insufficiency reported in several countries. Chapters II and III correspond to Scientific Productions I and II, respectively, and are part of the study “Vitamin D levels in individuals assisted at a Primary Health Care Unit (UBS),” approved by the Research Ethics Committee of the University of Passo Fundo (CEP/UPF), under protocol CAAE 82577924.6.0000.5342. This cross-sectional, descriptive, and exploratory study employed a semi-structured questionnaire and laboratory tests to determine plasma vitamin D levels, enabling the investigation of sociodemographic, clinical, lifestyle, medication use, and sun exposure variables among individuals assisted at the UBS in Coxilha, Rio Grande do Sul—a small municipality with a rururban profile. This dissertation made it possible to assess plasma levels of 25hydroxyvitamin D and associated factors among individuals assisted at a Primary Health Care Unit in a small rururban municipality. Consequently, it allowed the local health team to prescribe supplementation to those in need, positively impacting health promotion and overall well-being. The findings underscore the relevance of active surveillance, the importance of valuing local data for the formulation of evidence-based public health policies, and the need for further studies to deepen knowledge on vitamin D levels in populations with rururban characteristics.